Developing the Compressive Sensing Basis Matrix by Employing the Music Key as a Watermark and Acquire the Audio Signal - Electa Alice Jayarani.A, Mahabaleswara Ram Bhatt , Geetha. D.D (International Journal of Advanced Science and Technology, 2020)
To protect the multimedia files from hackers, various techniques such as watermarking and cryptography have been used. The protection of audio multimedia files is very tedious, as small changes in the audio can affect the quality of the audio file. Thus, it became a challenge for the researchers. To acquire the audio signal, we propose the compressive sensing rather than the traditional Nyquist sampling. In this article, we propose atechnique to embed the watermark onto the basis matrix of the compressive sensing and then acquire the audio signal with the embedded basis matrix.Keywords: Audio, Compressive sensing, basis matrix, multimedia.